Hepatic lesions: morphologic and functional characterization with multiphase breath-hold 3D gadolinium-enhanced MR angiography : initial results - Hawighorst, Hans; Schönberg, Stefan; Knopp, Michael V.; Essig, Marco; Kaick, Gerhard van (Radiology, 1999)
PURPOSE: To investigate multiphase (arterial, portal venous, and late venous phases) breath-hold three-dimensional (3D) gadolinium-enhanced magnetic resonance (MR) angiography for the detection and functional characterization of hepatic lesions.
Gesehen am 18.02.2021